Self-Efficacy and Collective Efficacy on the Students’ Correspondence Skill Based on Self-Determination Theory - Sansabu, Harina; Tusyanah, Tusyanah (Business and Accounting Education Journal, 2025)
Communication is an important skill that must be developed in an individual. In the context of the world of work, written communication skills are known as correspondence. This study aimed to enhance students' correspondence skills by investigating the impact of collaborative skills, engagement, and interpersonal communication on learning outcomes for office administration students. This research is a quantitative study. The population was 150 university students of office management. It was saturation sampling. The respondents who filled out the questionnaires were 141. Students filled out a questionnaire to measure self-efficacy and collective efficacy, whereas a test measured correspondence skills. The data were tabulated and analyzed using covariance-based SEM (CB-SEM). The results showed that based on SDT, self-efficacy and competence have a significant role in improving correspondence skills, while autonomy and relatedness influence self-efficacy and collective efficacy more. However, not all of them have a direct effect on correspondence learning outcomes. Therefore, to improve correspondence skills, it is essential to create a learning environment that supports increasing students' competence and self-confidence, as well as providing freedom in learning and communicating.